Development of infographic video media on biodiversity materials subchapter biodiversity for the ten-grade students - Zulham Tri Setyo; Arif Didik Kurniawan; Ari Sunandar (JPBIO (Jurnal Pendidikan Biologi), 2022)
The impact of the COVID-19 pandemic is very much felt in learning activities in schools so there is a need for appropriate learning media to make it easier for students to capture learning material. This study aims to determine the development of infographic video media in ten-grade IPA SMA Muhammadiyah 1 Pontianak. The research instrument used was a material expert validation questionnaire and a student response questionnaire. This type of research is Research and Development (R&D) model four D (Define, Design, Development, Dissemination). The results of the analysis show that the infographic video media developed is valid based on the validation results of media, material, and language experts. The percentage of validity of media, material, and language experts are 95.83%, 90.87%, and 97.50%, respectively, with very valid criteria, that can be used but need minor revisions. The percentage of the results of the questionnaire responses to the small-scale test and the large-scale test were 80.65% and 83.59%, respectively, with very strong criteria. This shows a positive response from students. Thus, the infographic video media that has been developed is appropriate to be used as a teaching medium for the material on biodiversity in ten-grade IPA SMA Muahmmadiyah 1 Pontianak.